Arte na educação infantil e o desenvolvimento das funções psíquicas superiores - Caram, Adriana Maria (Universidade Federal de São Carlos, 2015)
This research aims to analyze and discuss mediating activities that use Art in Childhood Education as a way to promote the development of the Higher Psychical Functions. The research was led by the following question: What role Art plays in children formation during Childhood Education? Both theoretical and methodological references were based on the Historical-Cultural Theory because it makes possible a conception of the human cultural development that sets Art as a human production; a space for social reflection and social internalization. Interviews with seven teachers from the municipal childhood education system and some pedagogical practices observations were used as methodological instruments. Led by this methodology, the analysis shows that both students and teachers have a very limited access to Art; it also shows that the teachers’ formation does not make Art a priority and, even though it occupies a very important place in class planning, it is still not considered an instrument for the catharsis. By going deeper in the analysis about the relations performed by teachers using Art in Childhood Education and the development of Higher Psychical Functions on children the study faced some ambiguous and sometimes contradictory situations. The activities suggested to the children, although undeniable creative, sometimes came to be fragmented and very poor to the goals of children’s development. However we were able to show in the research some actions that can be considered positive in the development of Higher Psychical Functions on children, contributing for a necessary reflection about the work with Art in Childhood Education, always led by the Historical-Cultural Theory, and promoting some interventions to improve the Higher Psychical Functions on children.
Art in childhood education and the development of higher psychic functions
Keywords: Arte na educação infantil; Funções psíquicas superiores; Formação docente; Teoria histórico-cultural; Art in childhood education; Higher psychical functions; Childhood education; Teacher formation; Historical-cultural theory; CIENCIAS HUMANAS::EDUCACAO